An examination of tactics used by ZANLA to promote their ideology and agenda for the liberation of Zimbabwe: a case study of Muzarabani (1972-1979) - Bomani, Thelma B. (Midlands State University, 2018)
ZANLA was the armed wing of ZANU, one of the two liberation movements that led the Zimbabwean liberation war. The ZANLA forces adopted the Maoist “fish and water” doctrine along with the Mao’s principles of People’s War in their contest against the Rhodesian army. The reason why the ZANLA cadres choose this warfare strategy was obviously to come out triumphant against the Rhodesian super forces. Guerrilla warfare was adopted for the need of the continued survival of the guerrillas, a prerequisite for realization of a preferred goal. This study examines tactics used by ZANLA forces that guaranteed their survival and victory against the Rhodesian forces in Muzarabani. These include an alliance between the ZANLA forces and the rural civilians as well as the unconditional revolutionary support from outside the country. The study also looked at the counter insurgency operations which the Rhodesian government deployed as a way of avenging and retaliating to the ZANLA warfare strategies and tactics as well as its effects on Muzarabani. The researcher used published books such as those projects written by Hushim Mbita and Fay Chung. They talked about how ZANLA cadres survived during the war of liberation and also the books written by Mao Tse Tung which analyse the main characteristics and strategies of a people’s war. These books gave the researcher a clear understanding of the reasons why the ZANLA forces adopted the guerrilla warfare. The dissertation used qualitative technique as a methodology of the study.